The Urgency of Digital Literacy in Improving Teacher Performance: A Case Study In Lebak Regency, Indonesia - Karim, Abdul; Sudadio, Sudadio; Juansah, Dase Erwin (Universitas Ahmad Dahlan, 2026)
Background. The rapid development of information and communication technology has transformed the educational landscape, requiring teachers to possess adequate digital literacy skills to optimize the learning process. In Lebak Regency, the diversity of geographical conditions and technological infrastructure raises questions about the extent to which digital literacy affects teacher performance. This study aims to analyze the effect of digital literacy on junior high school teachers’ performance in the region. Methods. Using a quantitative approach and a correlational survey method, data were collected from 120 purposively sampled teachers representing three geographical zones. The research instrument was validated and tested for reliability before use. Data analysis employed descriptive statistics and simple linear regression. Results. The results showed that digital literacy had a significant and positive effect on teacher performance, contributing 48.6%. Teachers with high digital literacy demonstrated better abilities in planning, implementing, and evaluating learning activities. Most respondents were in the high digital literacy category, although a small portion remained at a low level, particularly in areas with limited technological access. Conclusion. This study provides novelty by quantitatively analyzing this relationship within a specific subnational context (Lebak Regency) characterized by significant geographical and infrastructural disparities, a gap often overlooked by previous national-level or urban-focused research. The findings imply a critical need for a dual intervention policy that requires local government to not only improve equitable ICT infrastructure but also design adaptive professional development programs focused on contextual digital pedagogy to bridge the persistent competency gap